’Free from all possibility of historical error’: Orillia’s Champlain Monument, French-English Relations, and Indigenous (Mis)Representations in Commemorative Sculpture - Stevenson, Michael (Ontario History, 2017)
The 1925 unveiling of the Champlain monument in Orillia capped nearly three decades of public commemoration of Samuel de Champlain’s explorations in North America. Promoted tirelessly by local entrepreneur Charles Harold Hale and designed by English sculptor Vernon March, the monument was beset by controversy, construction delays and cost overruns. Nonetheless, when completed, it was initially greeted with nearly unanimous international acclaim. Two overarching themes marked the monument. First, its backers sought to use it to improve frayed relations between Ontario’s anglophone and Quebec’s francophone populations. Second, the monument’s design misrepresented the mutually beneficial relationship between Champlain and his Huron allies and promoted Eurocentric and colonial mentalities that marginalized the Indigenous contribution to the development of New France and Canada. While the first goal was largely unrealized, the second has resonated down to the present day.